Peran Key Performance Indicators (KPI) dalam Meningkatkan Kualitas Pelayanan Rumah Sakit: Literature Review - Vera Rizki Yuniar; Keysya Alifia Zabina; Medica Normalika Zakiah; Anita Wulansari (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Key Performance Indicators (KPIs) are performance measurement tools that evaluate how well an organization achieves its stated goals. In hospitals, KPIs can be used to improve the quality of health services. This literature review aims to determine the role of KPIs in improving the quality of hospital services by identifying factors that influence the preparation, implementation, and evaluation of KPIs. The method used is to collect and analyze scientific articles that are relevant to the research topic. The literature review results show that KPIs can benefit hospitals in terms of efficiency, effectiveness, and patient satisfaction. This literature review is expected to provide insights and references for hospitals that want to develop and implement KPIs as a performance measurement tool and improve service quality.